Polychaeta collected by U.D. Gaikwad at Ratnagiri, south of Bombay - Day, J. H. (Zoological Journal of the Linnean Society, London, 1973)
A collection of polychaete worms, obtained by Mr U. D. Gaikwad from sandy and rocky shores near the Ratnagiri Marine Biological Station which is some 240 km south of Bombay, included 50 species. Among them were seven new species namely: Intoshella indica, Hotolepidella rnaculata, Lepidasthenia tubicoh, Nereis (Nereis) gaikwdi, Polydora gaikwadi, Cirrntulus indicus, and Sabelluria simplex. The remaining species belong to the Indo-west Pacific fauna but several have not previously been recorded from India itself. Glycera decipiens Marenzeller, Dorvillea matsushimaensis (Okuda & Yamada) and Mesochaetopterus japonicus Fujuwara, known only from Japan, have been re-described. Nicolea gracilibranchis Grube is shown to be a synonym of the widely distributed N. wnustula (Montagu) and Terebella yappensis Okuda, originally described as a variety of T. ehrenbergi, is raised to species rank.
Kristian Fauchald's Polychaeta DB